Adhesion force of W dust on tokamak W plasma-facing surfaces: The importance of the impact velocity. (January 2019) - Autricque, A.; Gensdarmes, F.; Peillon, S.; Sow, M.; Grisolia, C.
Highlights: W/W dust-surface impacts always involve irreversible plastic deformation. For sticking impacts, the contact area, hence the adhesion force, depends on the impact velocity through the amount of plastic deformation. The dependence of the adhesion force on the impact velocity for W/W impacts is estimated. Weakening of the adhesion force by surface roughness is incorporated. Abstract: The adhesion of tungsten (W) dust particles on W tokamak plasma-facing surfaces is investigated. When spherical dust hits the tokamak walls, its shape is altered as a contact area is created by the adhesion work and irreversible plastic deformation. The van der Waals adhesion force between such a deformed grain and a flat surface is estimated, and the link between the force and the impact velocity is determined. We show that adhesion can be increased by several orders of magnitude when the impact velocity approaches the adhesion velocity. Finally, the effects of surface roughness are incorporated.